Effect of Foliar Organic Fertilizer on Caisim (Brassica junceae L) Growth and Yield - Sugeng Haryanto; Helda Sabban (TECHNO: JURNAL PENELITIAN, 2021)
The Caisim vegetable crop (Brassica chinensis) is a commodity that has commercial value and is a favorite commodity for some people in Indonesia. The demand for Caisim crop is expected to increase along with population growth with increased purchasing power. Moreover, Caisim crops are easily available in the market. The study determines the effect of treatments of foliar organic fertilizer application time on growth rate and production rate of Caisim (Brassica juncea L) crops. The research carries out in Gambesi, South Ternate from July to September 2020. Caisim crops in the beds are treated with morning fertilizing using foliar fertilizer. The research uses a randomized block design of 5 treatments and 3 replications. The 15 treatment units, namely P0 = without fertilization (control), P1 = application time at 6.00 - 7.00 WIT, P2 = application time at 7.00 - 8.00 WIT, P3 = application time at 8.00 - 9.00 WIT, and P4 = application time at 9.00 - 10.00 WIT. All treatments (P1, P2, P3, and P4) use the same dose of 2 cc/liter of water. The results indicate that the treatment P1 (6.00 - 7.00 WIT) has an excellent effect on fertilizer application times because it has a significant effect on crop height, the number of leaves, leaf area, and fresh weight compared to treatment P0, P2, P3, and P4.